PRODUCTION AND PURIFICATION OF CHITINASE FROM AEROMONAS SPP. AND STUDY ITS EFFECT ON SOME CANCER CELL LINES IN VITRO - & Nema, Hashim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Three hundred samples of stools were collected from children who are suffering from diarrhea. Twelve of them (4%) were positive for Aeromonas spp. test, the ability of Aeromonas isolates to produce chitinase enzyme was tested on medium supplemented with colloidal chitin. Chitinase enzyme was extracted, the crude extract activity and specific activity was 13 U/ml and 7.3 U/mg respectively. The enzyme was purified by precipitating with ammonium sulfate 70% saturation followed by ion exchange chromatography using DEAE- cellulose column and gel filtration chromatography using Sephadex G-200 column. The specific activity reached 154.5 U/mg with 21.16 purification fold and yield of enzyme was 52.3%. The molecular weight of the purified chitinase was 48 kDa when determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis )SDS-PAGE(. Cytotoxicity effects of chitinase enzyme on different normal and cancer cell lines were investigated by MTT assay. The results showed that the chitinase has a cytotoxic effect on breast cancer cells line (MCF-7) at concentration of 300 µg /ml., and it was cytotoxic to prostate cancer cell line (PC-3) at 400 µg/ml. Whereas it showed no cytotoxic effect on normal embryonic liver cell line (WRL-68).